Pandangan dan Peran Tokoh Kongres Ulama Perempuan Indonesia (KUPI) dalam Mencegah Perkawinan Anak - Ulfiyati, Nur Shofa (De Jure: Jurnal Hukum dan Syari'ah, 2019)
The permitted dispensation of a child marriage has to have a deep and serious consideration. A child marriage due to the dispensation from the court still mostly happens in Indonesia. The age of marriage written in the law has been considered irrelevant. Due to that issue, Indonesia’s Woman’s Scholars Congress (KUPI) has successfully published the instructions of three big issues; sexual abuse, early-age marriage, and natural damage. This research took the focus on how the view and the role of Indonesia’s Woman Scholar is toward the phenomenon of a child marriage. This research was a qualitative-descriptive research that captured the view of the personage of Indonesia’s Woman Scholars. The premier data were taken from the result of interviews from three personages of KUPI, they were Dr. Nur Rofi’ah, Nyai Hj. Umdatul Choirat and KH. Husein Muhammad. The result of this research showed that Woman Scholars have come with the view that a kid born from a weak mother has the potential to give birth to a weak baby too. As the result, child marriage is far from gaining the real purpose of marriage. Therefore, it can be strongly inferred that minimizing child marriage is compulsary.